(untitled) (Acta Entomologica Serbica, 2022)
Fauna of the subfamily Cremastinae Förster, 1869 (Ichneumonidae: Hymenoptera) on the territory of Turkey was investigated. The survey was conducted during the period 1995-2020. A total of 54 species belonging to eight genera have been listed. Among the material collected in the past 25 years, the species Cremastus brevicornis Kolarov & Beyarslan, 1999; C. kasparyani Kolarov Gürbüz & Birol, 2014; C. petiolaris Kolarov & Beyarslan; 1999; C. tristator Aubert, 1970; Nothocremastus beyarslani Kolarov, 1997 and Temelucha turcata Kolarov & Beyarslan, 1999 were listed as endemic to the investigated teritorry. Additionally, a male of Eucreamastus priebei Kolarov, 1999 is recorded for the first time from Turkey. Turkish species of the subfamily Cremastinae have been analyzed according to biogeographical and zoоgeographical features.